Beyond the definition of formal care: Informal care arrangements among older swedes who are not family. (3rd December 2019) - Siira, Elin; Rolandsson, Bertil; Wijk, Helle; Wolf, Axel
Abstract: This study explores care practices of older people outside formal care and without appealing to predefined relationships. We conducted interviews with 30 independent‐living men and women aged 67–93 in three municipalities in Sweden. The interviews explored how they cared for themselves and other older people who were not family. Interviews were conducted between December 2017 and May 2018 and later transcribed and analysed using grounded theory. Our paper presents one of the first studies on informal care practices among older people that looks beyond the definition of formal care to understand how such care complements formal care services. The findings show that older people participate in several care arrangements to care for themselves as well as for others. The arrangements feature different types of mutuality and include distant relations to other older people and larger more or less formalised groups. The findings highlight the importance of looking beyond conceptualisations of care based on understandings of formal care and specific relationships as a frame for understanding informal care. To promote older people's health by cultivating and supporting older people's care for themselves and others, research and healthcare practitioners need to explore and acknowledge the significance and complexity of older people's everyday care practices.